2021
DOI: 10.1002/jid.3587
|View full text |Cite
|
Sign up to set email alerts
|

The New Economic Geography and labour emigration: Analysing Venezuela's hyperinflation episode

Abstract: The Venezuelan hyperinflation process has caused serious economic and social consequences. The wave of migrants and refugees fleeing the country is one of the most obvious and important faces of the problem, with significant regional impacts. This paper aims to develop a methodology, related to the New Economic Geography, to explain Venezuelan labour migration flow from changes in the price level. Results from the model's simulations show that in the short run (1‐year horizon), Venezuelan industrial and agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
1
1
0
1
Order By: Relevance
“…A first notable element is the accounts of extremely tough living conditions amid the crisis in Venezuela, manifested in long lines to obtain food in limited quantities, difficulties in feeding the entire family, and the impossibility of finding medication for any family members with serious illness. These aspects coincide with recent research on the crisis in this country (Caraballo-Arias et al, 2018; Mazuera-Arias et al, 2020; Posso et al, 2023; Rocha et al, 2022; Van Roekel and De Theije, 2020) and the disproportionate toll it takes on children, adolescents, and their families (Carroll et al, 2020; Clauss-Ehlers, 2019; Pico et al, 2021; Pires et al, 2022; Vargas-Machuca et al, 2019). There were some socioeconomic differences between the adolescents based on their parents’ socio-professional level and type of employment: between those whose parents worked as laborers or as domestic workers and pertained to the popular classes, and those who were entrepreneurs or executives and corresponded to the (upper-) middle class.…”
Section: Concluding Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A first notable element is the accounts of extremely tough living conditions amid the crisis in Venezuela, manifested in long lines to obtain food in limited quantities, difficulties in feeding the entire family, and the impossibility of finding medication for any family members with serious illness. These aspects coincide with recent research on the crisis in this country (Caraballo-Arias et al, 2018; Mazuera-Arias et al, 2020; Posso et al, 2023; Rocha et al, 2022; Van Roekel and De Theije, 2020) and the disproportionate toll it takes on children, adolescents, and their families (Carroll et al, 2020; Clauss-Ehlers, 2019; Pico et al, 2021; Pires et al, 2022; Vargas-Machuca et al, 2019). There were some socioeconomic differences between the adolescents based on their parents’ socio-professional level and type of employment: between those whose parents worked as laborers or as domestic workers and pertained to the popular classes, and those who were entrepreneurs or executives and corresponded to the (upper-) middle class.…”
Section: Concluding Discussionsupporting
confidence: 87%
“…Since 2016 Latin America has witnessed the mass exodus of families from Venezuela as a result of the deteriorating living conditions in their home country. The collapse in the price of petrol; hyperinflation and the contraction of consumption; food and medication shortages; and deficiencies in the supply of public utilities such as water, gas, and electricity were the major components of a humanitarian crisis that precipitated emigration on a scale that the region had not previously experienced (Caraballo-Arias et al, 2018; Gandini et al, 2020; Mazuera-Arias et al, 2020; Posso et al, 2023; Rocha et al, 2022; Van Roekel and De Theije, 2020). In addition to an unprecedented increase in infant mortality during the 2013–2016 period (García et al, 2019), Venezuela’s Living Conditions Survey (Encuesta de Condiciones de Vida, ENCOVI) revealed that 91% of the population were below the poverty line in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Desde 2016, la deteriorada situación económica y social en Venezuela ha generado una oleada masiva de emigraciones hacia los países de la región. La disminución del precio del petróleo, la hiperinflación y la contracción del consumo, la escasez de alimentos y medicinas, la falta de servicios públicos, así como los problemas de suministro de agua, gas y electricidad, y las dificultades en materia de seguridad y respeto de los derechos humanos, conforman los principales elementos de lo que se ha denominado una "crisis humanitaria" (Castillo Crasto y Reguant Álvarez, 2017;John, 2019;Mazuera-Arias et al, 2020;Posso et al, 2022;Rocha et al, 2022;Wallace y Mortley, 2021). Este contexto ha provocado en particular un aumento en la mortalidad infantil (García et al, 2019), una generalización de la pobreza y de la inseguridad alimentaria 1 , así como la migración de un gran número de mujeres embarazadas que ya no encontraron las condiciones mínimas de atención médica en su país de origen (Hawkins Rada, 2022).…”
unclassified